A Novel Cable-Driven 7-DOF Anthropomorphic Manipulator - Huang, Yanjiang; Chen, Yanlin; Zhang, Xianmin; Zhang, Hongchuan; Song, Chunyu; Ota, Jun (IEEE/ASME transactions on mechatronics, 2021)
Safety design of robot arm is important for human-robot interaction. In this article, an anthropomorphic seven-DOF cable-driven manipulator, including a three-DOF shoulder joint module, a one-DOF elbow joint module, and a three-DOF wrist joint module, is proposed for human-robot interaction. These three joint modules are connected serially and the motion transmission is realized by rope. The joint stiffness and workspace of joint module are numerically analyzed and compared to that of the human arm joint. A protype of manipulator is machined and used to evaluate the joint stiffness and workspace of the joint module through experiments. The mass of the designed manipulator is approximately 4.8 kg, which is similar to that of a human arm. The stiffness of elbow joint is 185.25 N·m/rad in positive direction and 133.75 N·m/rad in negative direction, which is smaller than that of the human elbow joint. The stiffness of wrist joint is 48.25 N·m/rad. The stiffness of shoulder joint under two configurations is 138 and 124 N·m/rad. The workspace matching index (WMI) is used to evaluate the workspace of joint module by comparing to that of the human arm joint. The WMI of the developed shoulder joint is approximately 40% of the human shoulder joint due to the structure constraint. While the workspaces of the developed elbow joint and wrist joint are the same with that of human joint.